2021
DOI: 10.51601/ijcs.v1i3.45
|View full text |Cite
|
Sign up to set email alerts
|

Urban Community Engagement to Reduce and Prevent Food Waste at Household Level

Abstract: Indonesia faces a food waste problem, particularly at the household level. Food waste causes negative impacts on several aspects such as environment, society, and economy. Ironically, at the same time, Indonesia also has a serious hunger problem. Through community development programs, we aimed to empower households in recycling their food waste by eco enzyme and their awareness through an online challenge. Eco enzyme is an affordable and useful method to recycle food waste being a liquid product with many ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…so that it can draw in a sizable audience for its online campaigns and seminars. A challenge that fosters positive relationships between participants and the organizers can be held by launching an online campaign [40]. Furthermore, the online campaign/seminar approach utilizes technology, particularly social media.…”
Section: Figure 2 the Article Type Of Food Waste Communitymentioning
confidence: 99%
See 1 more Smart Citation
“…so that it can draw in a sizable audience for its online campaigns and seminars. A challenge that fosters positive relationships between participants and the organizers can be held by launching an online campaign [40]. Furthermore, the online campaign/seminar approach utilizes technology, particularly social media.…”
Section: Figure 2 the Article Type Of Food Waste Communitymentioning
confidence: 99%
“…The urban community has also conducted this education program in the form of the campaign "DIY: Eco Enzyme," which persuades participants to recycle their food waste. Through this education program, many people would be influenced, and the climate action goal in the SDGs could be achieved [40], [51].…”
Section: Figure 4 the Target Audience Of Community Educationmentioning
confidence: 99%
“…It also has not discussed social media as a potential method to reduce food waste. Contrary to the first research, the second research shows workshops and social media content regarding food waste [5]. Although it discusses both methods, there are several crucial contents that have not been listed in the online campaign.…”
mentioning
confidence: 98%
“…Community advertising and success story spread potentially occur to improve audience comprehension regarding food waste [4]. Other research found that offline workshops and online campaigns through social media can engage several audiences to raise their awareness [5]. This is also done through community development programs.…”
mentioning
confidence: 99%
See 1 more Smart Citation